2011
DOI: 10.1007/s12038-011-9089-y
|View full text |Cite
|
Sign up to set email alerts
|

The Chriz–Z4 complex recruits JIL-1 to polytene chromosomes,a requirement for interband-specific phosphorylation of H3S10

Abstract: The conserved band-interband pattern is thought to reflect the looped-domain organization of insect polytene chromosomes. Previously, we have shown that the chromodomain protein Chriz and the zinc-finger protein Z4 are essentially required for the maintenance of polytene chromosome structure. Here we show that both proteins form a complex that recruits the JIL-1 kinase to polytene chromosomes, enabling local H3S10 phosphorylation of interband nucleosomal histones. Interband targeting domains were identified at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…3D-F). In addition to SU(HW), L(3)MBT interacts with a chromodomain protein, Chromator, that has also recently been shown to colocalize and cooperate with the BEAF-32 insulator (Giot et al 2003;Gan et al 2011). Indeed, using publicly available ChIP-chip data for Chromator in Drosophila Kc cells (Celniker et al 2009), aligned dCTCF sites also show an apparent enrichment for Chromator (Fig.…”
Section: Aligned Dctcf Sites Are Enriched For Cp190 Mod(mdg4) Isoformentioning
confidence: 94%
“…3D-F). In addition to SU(HW), L(3)MBT interacts with a chromodomain protein, Chromator, that has also recently been shown to colocalize and cooperate with the BEAF-32 insulator (Giot et al 2003;Gan et al 2011). Indeed, using publicly available ChIP-chip data for Chromator in Drosophila Kc cells (Celniker et al 2009), aligned dCTCF sites also show an apparent enrichment for Chromator (Fig.…”
Section: Aligned Dctcf Sites Are Enriched For Cp190 Mod(mdg4) Isoformentioning
confidence: 94%
“…M1BP is a recently discovered zinc finger transcription factor that has been shown to orchestrate promoter-proximal pausing in a GAF-independent manner (Li and Gilmour 2013). BEAF-32 is one of the insulator-associated proteins identified in Drosophila (Zhao et al 1995), Chromator was initially identified as a mitotic spindle protein and later implicated in the regulation of chromosome structure through partial cooperation with BEAF-32 (Rath et al 2006;Gan et al 2011), and both of these proteins are enriched at the boundaries of physical chromosomal domains (Hou et al 2012;Sexton et al 2012). The factor with the highest differential enrichment for promoterbound genes in our screen was the tandem kinase JIL-1 (Supplemental Table S6), which has been shown previously to interact with Chromator (Rath et al 2006).…”
Section: Insulator Proteins and M1bp Are Enriched In The Promoter Regmentioning
confidence: 99%
“…We observed prominent binding of Chriz, Z4 (data not shown) and Jil-1, proteins that are typically found in decondensed chromatin as reported previously (Eggert et al, 2004;Gortchakov et al, 2005;Wang et al, 2001). Chriz and Jil-1 physically interact (Rath et al, 2006), and on Chriz knockdown both Jil-1 chromosomal binding and H3S10 phosphorylation are dramatically reduced, indicating that Chriz is required for chromosomal targeting of Jil-1 (Gan et al, 2011). Forced local recruitment of active Jil-1 kinase results in local chromatin decondensation (Deng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Forced local recruitment of active Jil-1 kinase results in local chromatin decondensation (Deng et al, 2008). Hypomorphic mutations in Jil-1 and Chriz, by contrast, result in chromosome condensation and loss of interphase chromatin structure (Wang et al, 2001;Rath et al, 2006, Gan et al, 2011, similar to what is observed on loss of Z4 protein (Eggert et al, 2004). Besides these factors, we observed binding of the insulator proteins CP190 (Whitfield et al, 1988;Pai et al, 2004) and BEAF 32 (Zhao et al, 1995; data not shown) to the ectopic 61C7-8 position, resembling the situation at the endogenous site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation